Fe containing silica gel catalysts for catalytic wet peroxide oxidation processes - Gomes, Helder (2010)
The degradation of pollutants by catalytic wet peroxide oxidation (CWPO) using the Fenton’s reagent is a well known process, the major drawback being the need to recover the iron catalyst at the end of treatment. To overcome this, new heterogeneous catalysts have been developed and studied since some years ago, which involve the incorporation of iron species into a solid matrix [1-2]. In this work we aimed to develop Fe containing silica gel catalysts (5wt. % Fe) using sol-gel techniques and to test their suitability for the CWPO of azo dye Chromotrop 2R aqueous solutions.